2020
DOI: 10.1016/j.ijid.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

LIOFeron®TB/LTBI: A novel and reliable test for LTBI and tuberculosis

Abstract: A B S T R A C TObjectives: High accuracy diagnostic screening tests for tuberculosis (TB) are required to improve the diagnosis of both active TB and latent Mycobacterium tuberculosis (MTB) infection (LTBI). The novel IGRA LIOFeron 1 TB/LTBI assay was tested and its accuracy was compared to the QuantiFERON 1 -TB Gold Plus assay. Methods: A total of 389 subjects were enrolled in two cohorts and classified as healthy, active TB or LTBI persons. The blood of all the patients was tested with LIOFeron 1 TB/LTBI ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…To overcome the deficiencies of the TST, IGRAs have been developed as an alternative immunodiagnostic approach. Thus far, there are five commercialized IGRA kits, including the T-cell spot of the TB assay (T-SPOT.TB, Oxford Immunotec, Abingdon, UK), QuantiFERON-TB Gold In-Tube (QFT-GIT, Qiagen GmbH, Hilden, Germany), QuantiFERON-TB Gold-Plus (QFT-Plus, Qiagen, MD, United States), LIAISON QuantiFERON-TB Gold Plus (LIAISON QFT-Plus, DiaSorin S.p.A., Italy), and LIOFeron TB/LTBI (LIONEX GmbH, Braunschweig, Germany) (De Maertelaere et al, 2020;Della Bella et al, 2020;Altawallbeh et al, 2021;Hamada et al, 2021). In addition, there are five products in development-T-Track (R) TB (Lophius Biosciences GmbH), VIDAS TB-IGRA (bioMérieux), Access QuantiFERON-TB (Boditech Med Inc.), ichroma TM IGRATB (Boditech Med Inc.), and IP-10 IGRA elisa/lateral flow (rBioPharm) (WHO, 2020).…”
Section: Interferon-gamma Release Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the deficiencies of the TST, IGRAs have been developed as an alternative immunodiagnostic approach. Thus far, there are five commercialized IGRA kits, including the T-cell spot of the TB assay (T-SPOT.TB, Oxford Immunotec, Abingdon, UK), QuantiFERON-TB Gold In-Tube (QFT-GIT, Qiagen GmbH, Hilden, Germany), QuantiFERON-TB Gold-Plus (QFT-Plus, Qiagen, MD, United States), LIAISON QuantiFERON-TB Gold Plus (LIAISON QFT-Plus, DiaSorin S.p.A., Italy), and LIOFeron TB/LTBI (LIONEX GmbH, Braunschweig, Germany) (De Maertelaere et al, 2020;Della Bella et al, 2020;Altawallbeh et al, 2021;Hamada et al, 2021). In addition, there are five products in development-T-Track (R) TB (Lophius Biosciences GmbH), VIDAS TB-IGRA (bioMérieux), Access QuantiFERON-TB (Boditech Med Inc.), ichroma TM IGRATB (Boditech Med Inc.), and IP-10 IGRA elisa/lateral flow (rBioPharm) (WHO, 2020).…”
Section: Interferon-gamma Release Assaysmentioning
confidence: 99%
“…Previous studies have reported that Ala-DH is absent in BCG, induces major histocompatibility complex (MHC) class I-restricted T CD8 + lymphocytes to produce IFN-γ, and participates in the adaptation of M. tuberculosis to the anaerobic dormant stage in LTBI (Jungblut et al, 1999;Dong et al, 2004;Agren et al, 2008). Recently, the sensitivity and specificity of the novel test were evaluated, and a comparison between its accuracy and that of the QFT-PLUS assay was performed in patients with aTB and LBTI (Della Bella et al, 2020). The results demonstrated that the sensitivity and specificity of the LIOFeron TB/LTBI assay was 90% and 98% for diagnosing aTB and 94% and 97% for diagnosing LTBI and that the LIOFeron TB/LTBI assay showed higher sensitivity than the QFT-Plus test for LTBI detection (Della Bella et al, 2020).…”
Section: Lioferon Tuberculosis/latent Tuberculosis Infection Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…IGRA by detecting IFNγ released by T cells exposed to TB antigens, has been found more sensitive than the traditional methods to diagnose acute and latent TB, even in immunocompromised patients [ 24 , 25 ]. New generations of IGRA were found even more sensitive than their earlier generations [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Millions of patients with LTBI are underdiagnosed every year, 36 37 and there is an urgent need for better diagnostic tools. 38 The quick differentiation and correct identification of ATB from LTBI is the current focus of global tuberculosis prevention and control. Blood and urine are good sources of samples for diagnosis without causing harm to the human body.…”
Section: Discussionmentioning
confidence: 99%